Studies on mosquitoes (Diptera: Culicidae) and anthropic environment: 6 - Breeding in empty conditions of rice fields in South-Eastern Brazil - Oswaldo Paulo Forattini; Iná Kakitani; Eduardo Massad; Daniel Marucci
Studies on culicid breeding in empty rice fields were carried out during the cultivation cycle from May to November 1993. This period corresponded to stages 1 and 2, when empty conditions prevailed. Breeding occurred in stage 1 and the first part of stage 2, corresponding respectively to fallow uncultivated and ploughing situations. No breeding was found to take place during the second part of stage 2 when transient floods and harrowing occurred. The predominant species were Aedes scapularis, Culex nigripalpus and Cx. mollis. The Pilosus Group of Culex (Melanoconion) was found at lower densities. Some epidemiological considerations are presented.